2020
DOI: 10.1021/acsanm.0c02615
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Forbidden Light Propagation in Nanoporous Anodic Alumina Gradient-Index Filters by Alcohol Additives

Abstract: A comprehensive study on structural and optical engineering of high-quality nanoporous anodic alumina gradientindex filters (NAA-GIFs) by selective addition of alcohols to the anodizing acid electrolyte is presented. Analysis of the combined effect of type (methanol, ethanol, isopropanol, and ethylene glycol) and concentration (from 10 to 70 vol %) of alcohol additives in sulfuric acid electrolytes on the optical features of the characteristic photonic stopband of NAA-GIFscentral wavelength, full width at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…The PSB optical features of the structure such as the position of the central wavelength, the width at half-maximum, and the intensity could be adjusted by altering the time gaps-with the incidence angle of photons and the porosity of the structure being relevant as well. While the previous works involved 0.3 M oxalic acid, investigation regarding properties of photonic structures made with sulfuric acid and various additives (alcohols and polyols) is provided by Lim et al [150]. The comprehensive study revealed advantages of such approach.…”
Section: Structures Based On the Modulation Of The Anodization Currentmentioning
confidence: 99%
“…The PSB optical features of the structure such as the position of the central wavelength, the width at half-maximum, and the intensity could be adjusted by altering the time gaps-with the incidence angle of photons and the porosity of the structure being relevant as well. While the previous works involved 0.3 M oxalic acid, investigation regarding properties of photonic structures made with sulfuric acid and various additives (alcohols and polyols) is provided by Lim et al [150]. The comprehensive study revealed advantages of such approach.…”
Section: Structures Based On the Modulation Of The Anodization Currentmentioning
confidence: 99%
“…Recent efforts have focused on developing new forms of nanoporous semiconductor PCs to address these limitations for maximizing photocatalytic efficiency. Among these, anodization of aluminum enables the development of nanoporous anodic alumina (NAA)-based PCs based on engineered optical features throughout the spectrum. Although NAA is an electronic insulator ( i.e. , electronic band gap ∼9 eV) and cannot be directly applied in photocatalysis, functionalizing the nanoporous structure of NAA-PCs with light-responsive semiconductor layers has opened a new pathway to overcome this drawback.…”
Section: Introductionmentioning
confidence: 99%
“…65 during the electrochemical oxidation process. 39 The XRD spectrum of an as-produced NAA−PC shows three characteristic peaks located at 45, 65.2, and 78.4°, which correspond to amorphous alumina (Al 2 O 3 ) phase (Figure S3bSupporting Information).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The position of the PSB is critically determined by the distribution of effective optical thicknessthe product of physical thickness and effective refractive indexalong the NAA stacks forming the structure of NAA−PCs. 39 Judicious manipulation of T P in the input Laplacian and Lorentzian current density pulses makes it possible to precisely tune the position of the PSB across the spectrum, harnessing the inherent dependence of λ PSB with L TP . 59 For instance, increasing anodization period results in longer period length in the NAA−PCs (L TP in Figure 3c), which in turn shifts the PSB position toward longer wavelengths (i.e., red shift).…”
Section: Structuralmentioning
confidence: 99%